Celebrating 120 Years of Butantan Institute Contributions for Toxinology - Moura-Da-Silva, Ana Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This is collection of original and review articles selected in recognition of the contribution of Instituto Butantan to the field of toxinology and its continued and relevant role in this field in the 120 years since its foundation. Congratulations to the Butantan Institute, its house scientists, and collaborators on its 120th anniversary!